Wastewater Reuse - Mehta, Kushal (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Wastewater Reuse is that idea which basically deals with the treatment and reusing of wastewater from domestic areas for irrigation purposes. In this process, the wastewater which is being obtained from the domestic societies is being treated by the phragmite plants. These phragmite plants have an unique property of killing the harmful toxic micro-bacterial organisms from the wastewater and make it suitable for reuse. Actually the phragmite have the property of disintegrating the wastewater by their roots and make them suitable for the reuse. The quantity of wastewater obtained from societies is treated with the help of these plants which can be reused for different purposes like planting, gardening, irrigation, washing floors etc. The solid wastes are separated at the starting of the pipes through which wastewater goes to the tank. The solid wastes are collected at a place and mixed with fallen leaves and organic matters which after some days can be used as organic manures are fertilization which can be used in biogas-plants for producing biogas. In this way, wastewater is converted into suitable water and the other solid materials converted into biogas. So, this technique must be adopted at different societies.